(1)an+1-an=-
=(n≥2),
上式表明an+1-an与an-an-1同号,
∴an+1-an,an-an-1,an-1-an-2,…,a2-a1同号,
∵a>2,
∴a2-a-2=(a-2)(a+1)>0,
∴a2>a+2,
∴a2=<a,a2-a1<0.
∴an+1-an<0,
故an+1<an.
(2)∵an+1=bn+1+
=
=,
bn+12+=bn+,
bn+14-(bn+)bn+1 2+1=0,
注意到bn>1,
f(x)=x+(x>0),f′(x)=1->0,
∴f(x)在x>1时为增函数,而f(bn+12)=f(bn),
∴bn+12=bn,
∴2lgbn+1=lgbn,
∴=,
∴数列{lgbn}是等比数列,
当a1=b1+=,b1=,lgb1=lg,
lgbn=()n-1•lg=()n•lg2,
∴bn=2()n,
an=bn+=2()n+2-()n.
(3)∵当n≥2时,an-2=-2=,
上式表明:an-2与an-1-2同号,对一切n≥2成立,
∴an-2,an-1-2,…,a2-2,a1-2同号,
而a1-2>0,
∴an-2>0,an-1-2>0,
∵n≥2时,an-2=<=,
∴<,
∴•…•
=<()n-1,
∴0<an-2<(a1-2)•()n-1,
当a1=2011,n=12时,
a12-2=(2011-2)×()12-1=<=<,
∴a12<2+,
∵an>an+1,
∴当n≥12时,2<an<2+恒成立.